Effect of the Variations of Molasses Concentration And Corn Flour on Growing Media for White Oyster Mushroom (Pleurotus Ostreatus) Productivity - Anggraini, Dina; Warsito, Kabul; Hafiz, Muhammad (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Oyster mushroom (Pleurotus ostreatus) can grow well on materials that contain carbohydrates. One of the fungal growth ingredients that contain carbohydrates is corn flour. In addition to corn flour, molasses can also be used to stimulate the growth of white oyster mushrooms. The purpose of this study was to see the effect of variations in the concentration of molasses and corn flour on the growing media on the productivity of white oyster mushroom (Pleurotus ostreatus). The research was conducted in May-July 2022 at the Center for Breeding and Development of Oyster and Ear Mushroom Cultivation on Sunggal District, Deli Serdang Regency. The research method used was a factorial completely randomized design (CRD) with 2 factors, 16 treatment combinations and 2 replications so that there were 32 baglogs. The first factor contained 4 levels of treatment, namely M0: 0 ml/baglog, M1: 7.5 ml/baglog, M2: 15 ml/baglog and M3: 22.5 ml/baglog. The second factor has 4 levels of treatment, namely J0: 0 gr/baglog, J1: 10 gr/baglog, J2: 20 gr/baglog and J3: 30 gr/baglog. Parameters observed were mycelium growth rate (cm), stalk height (cm), hood diameter (cm), hood thickness (mm), number of branches/clumps, wet weight (g). The results of the highest data mycelium growth rate in treatment J0 of 20.75 cm. The result of the highest data stalk height in the M1 treatment was 6.19 cm. The results of the highest data hood diameter in treatment J0 of 10.18 cm. The result of the highest data hood thickness in treatment J2 was 5.09 mm. The result of the highest number of branches/data clusters in the M3 treatment was 9.13 branches. The result of the highest wet weight (g) data in the M3 treatment was 140.75 gr.